THE IMPLEMENTATION OF CONVERSATION IMPROVEMENT ON FISHBOWL METHOD TO IMPROVE THE SPEAKING ABILITY OF STUDENTS: A CASE STUDY OF TEACHING EFL AT SMAN 2 KUPANG - Fransiskus Xaverius Ivan Rahas (Postgraduate School, Universitas Nusa Cendana, 2019)
This research was conducted in Class X of SMAN 2 Kupang in the academic year 2018/2019. The subjects in this study were 36 students of class X IPA 1 of SMAN 2 Kupang. This study aimed to determine the increase in English speaking skills of students by applying the fishbowl method based on conversation improvement. This type of research was qualitative with descriptive design. Data collection techniques used in this study were tests, observations, and speaking assessment sheets. The researcher observed what students did while having a conversation in class. The researcher used 4 (four) conversation improvement strategies. In the pra research, there were 31 students (86%) failed to reach the minimum completion criteria. In the first cycle, there was an increasing of the results of students' speaking skills where 41% students reached the minimum completion criteria. At this stage, students had not shown significant improvement in linguistics aspects (such as stress, speech, tone and rhythm) and non-linguistics aspects (such as fluency and mastery of the topic). The results of the first cycle were followed up by the second cycle. The results showed that there was an increasing in the the minimum completion criteria for 88%. There were also significant improvements in linguistics aspects (such as stress, speech, tone and rhythm) and non-linguistics aspects (such as fluency and mastery of the topic).